SEQUENTIAL SUBSTITUTION OF METHYL SIDE GROUP IN NAPTHOQUINONE AND ANTHRAQUINONE TO INVESTIGATE SENSITIVITY OF THE CARBONYL BAND - Raut, Nabin Kumar; Lamichhane, Hari Prasad (Journal of Institute of Science and Technology, 2017)
In this work, we have added methyl side group (s) on quinone and aromatic ring carbon positions of 1, 4-naphthoquinone (NQ) and on aromatic ring carbon positions of 1, 4-anthraquinone (AQ) in sequential increasing order to check sensitivity of the carbonyl band. In NQ, we observed that the aromatic substitution is more sensitive than the quinonic substitution. In fact, the sequential addition of CH3on the quinone ring C5 and C6 positions lead into the systematic lowering of the band and such lowering is in average of 5 cm-1 per methyl group. On the other hand, addition on the aromatic ring C7, C8, C9, and C10 positions resulted in mix effect. Indeed, they produce two types of carbonyl band, which are couple and uncouple. For further exploration of the sensitivity of the carbonyl band, we put single or two methyl group (s) on C7, C8, C9, and C10 carbon positions producing four or six NQ model molecules. We concluded that the carbonyl intense bands are more sensitive, split up, to the aromatic ring methyl substitution at C7 or C10 position. Furthermore, in AQ couple mode of C=O vibration was observed and no splitting of the band was seen on sequential CH3 addition. Journal of Institute of Science and Technology Volume 22, Issue 1, July 2017, Page: 137-146